Peningkatan Motivasi Belajar Siswa dalam Pembelajaran Microsoft Excel melalui Pembelajaran Kooperatif Tipe STAD di MAN 2 Yogyakarta - Fajar Rahmadi (Jurnal Pendidikan Madrasah, 2022)
This research aims to describe the application of cooperative learning using the STAD model in increasing student learning motivation at MAN 2 Yogyakarta. This research uses an action research method consisting of 4 stages, namely; planning, implementation of actions, observation and reflection. The subject of this study is class X IPS 2 students of the 2019/2020 school year with a total of 24 people, consisting of 7 male students and 17 female students. Data collection techniques use interviews, observations, documentation. The results showed that the application of STAD-type cooperative learning can improve student learning outcomes and activities in informatics subject excel materials. This can be proven by the percentage of achievements to student activity increased from 32.75% in the first cycle to 92.75% in the second cycle and can be declared successful because it has reached performance indicators.